Renal Safety of Intravenous Ketorolac Use After Donor Nephrectomy. (September 2019) - Tabrizian, Parissa; Giacca, Massimo; Prigoff, Jake; Tran, Benjamin; Holzner, Matthew L.; Chin, Edward; Palese, Michael; Herron, Daniel; Arvelakis, Antonios; Rudow, Dianne LaPointe; Florman, Sander; Shapiro, Ron
Introduction: The benefit and short-term safety of ketorolac have been established in previous studies however, the risk of bleeding and long-term renal impairment in patients undergoing donor nephrectomy remain unclear. We report our experience at a high-volume transplant center. Method: Between January 1996 and January 2014, 862 consecutive patients underwent laparoscopic donor nephrectomy. Exclusion criteria included nonsteroidal anti-inflammatory drug allergy, asthma, bleeding disorders, long-term opioid use, intraoperative blood loss >700 mL, peptic ulcer disease, bleeding diathesis, and baseline creatinine greater than 1.9 mg/dL. Intravenous ketorolac was administered within 30 minutes following the surgical procedure at a dose of 15 to 30 mg every 6 hours. Patients were categorized into 2 groups according to the administration of ketorolac after surgery. Differences between the groups were analyzed. Primary outcomes were changes in serum creatinine and hemoglobin levels. Poor outcome was defined as postsurgical complications. Results: During this time, 469 (55.3%) received ketorolac. The mean donor age was 39 years, and 360 (42.5%) were male. Left kidneys were procured in 82%. Operative time averaged 210 minutes and warm ischemia time117 seconds. Baseline demographic and operative outcomes were comparable in both groups. No statistically significant differences were found between the ketorolac group and the nonketorolac group in preoperative and postoperative hemoglobin levels and serum creatinine at 1 week, 1 year, and 5 years ( P = .6). Ketorolac use was not associated with increased perioperative morbidity ( P = NS). Conclusion: The use of intravenous ketorolac in patients undergoing donor nephrectomy was not associated with an increased risk of bleeding or renal impairment.